2012
DOI: 10.1007/s00442-012-2417-6
|View full text |Cite
|
Sign up to set email alerts
|

A long-term experimental test of the dynamic equilibrium model of species diversity

Abstract: The dynamic equilibrium model of species diversity predicts that ecosystem productivity interacts with disturbance to determine how many species coexist. However, a robust test of this model requires manipulations of productivity and disturbance over a sufficient timescale to allow competitive exclusion, and such long-term experimental tests of this hypothesis are rare. Here we use long-term (27 years), large-scale (8 × 50-m plots), factorial manipulations of soil resource availability and sheep grazing intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 58 publications
1
29
1
Order By: Relevance
“…In addition, our study showed stronger evidence for limiting similarity under lower grazing intensity, where competition for light is also expected to be higher because grazing can suppress competitive dominance (Grime ; Laliberté et al. ). Our results are consistent with those of Mason et al.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, our study showed stronger evidence for limiting similarity under lower grazing intensity, where competition for light is also expected to be higher because grazing can suppress competitive dominance (Grime ; Laliberté et al. ). Our results are consistent with those of Mason et al.…”
Section: Discussionmentioning
confidence: 59%
“…Grazing intensity was measured as the proportion of ANPP consumed (or destroyed) by sheep over the 18‐mo sampling period (Laliberté & Tylianakis ; Laliberté et al. ). Details of these measurements are available elsewhere (Laliberté & Tylianakis ; Laliberté et al.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Laliberté et al. () showed consistent changes in species richness with DEM predictions using a long‐term factorial manipulation of soil resources and grazing intensity. However, the same patterns do not necessarily hold for other diversity indices since they may not all be driven by the same underlying processes.…”
Section: Introductionmentioning
confidence: 69%
“…In addition, thick stubble and litter layers associated with quick regrowth may prevent individual recruitment in productive grasslands (Laliberté et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation